2018
DOI: 10.20533/iji.1742.4712.2018.0180
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Gender Gap in Financial Literacy

Abstract: Studies have repeatedly shown that women answer less financial knowledge questions correctly than men. Hence, they are often identified to be a financially 'vulnerable' group who needs more attention in financial education. This paper explores if this holds true for the Austrian population. A survey among 2,000 respondents reveals that Austrian men outperform women in terms of financial knowledge, even if we control for different socio-demographic characteristics and response behavior. However, women seem to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“… Gender may be considered as an antecedent of the financial literacy of undergraduate students. This is mainly in accordance with the findings of Erner, Goede-Menke and Oberste (2016), Tavares, Almeida and Cunha ( 2019), Garg andSingh (2018), Lusardi, Mitchell andCurto (2010), Chen and Volpe (1998), Bucher-Koenen et al (2014), Fonseca et al (2012), Yu, Wu, Chan and Chou (2015, Falahati and Paim (2011), Khurshed and Iftikhar (2014), Okičić and Kakeš (2019), Falahati andPaim (2011), Greimel-Fuhrmann andSilgoner (2018), etc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… Gender may be considered as an antecedent of the financial literacy of undergraduate students. This is mainly in accordance with the findings of Erner, Goede-Menke and Oberste (2016), Tavares, Almeida and Cunha ( 2019), Garg andSingh (2018), Lusardi, Mitchell andCurto (2010), Chen and Volpe (1998), Bucher-Koenen et al (2014), Fonseca et al (2012), Yu, Wu, Chan and Chou (2015, Falahati and Paim (2011), Khurshed and Iftikhar (2014), Okičić and Kakeš (2019), Falahati andPaim (2011), Greimel-Fuhrmann andSilgoner (2018), etc.…”
Section: Discussionsupporting
confidence: 89%
“…Many recent studies (Erner, Goede-Menke, & Oberste (2016), Tavares, Almeida, & Cunha (2019), Garg & Singh (2018), Lusardi, Mitchell, & Curto (2010), Chen & Volpe (1998), Bucher-Koenen et al (2014), Fonseca et al (2012), Yu, Wu, Chan, & Chou (2015), Khurshed & Iftikhar (2014), Okičić & Kakeš (2019), Falahati & Paim (2011), Greimel-Fuhrmann & Silgoner (2018, Oseifuah, Gyekye, & Formadi (2018), Kiliyanni & Sivaraman (2018), Agnew, Maras, & Moon (2018), Barboza, Smith, & Pesek (2016), Hasler & Lusardi (2017), etc. have shown that there is a potential gender gap in terms of financial literacy.…”
Section: Gender and Financial Literacymentioning
confidence: 99%
“…In particular, the consideration of individuals' socioeconomic environment may further help to explain the financial literacy gap between men and women. Prior research has observed that large differences in financial literacy persists between men and women even after controlling for a broad set of their sociodemographic characteristics (e.g., Greimel-Fuhrmann & Silgoner, 2018;Van Rooij et al, 2011) and has called for future research helping to explain this gap (Bucher-Koenen et al, 2017;Lusardi & Mitchell, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding socio-demographic data, results of most studies indicate a gender effect and generally men perform better than women in financial literacy tests (Chen and Volpe 2002;Mitchell 2011, 2014;Hung et al 2009;Atkinson and Messey 2012;Woodyard and Robb 2012;Agnew et al 2013;Bucher-Koenen et al 2014;Schuhen and Schürkmann 2014;Agnew and Harrison 2015;Almenberg and Dreber 2015;Filipial and Walle 2015;Bannier and Neubert 2016;Ergün 2017;Gramatki 2017;Hasler and Lusardi 2017;Killins 2017;OECD 2017;Strömbäck et al 2017;Förster et al 2018;Greimel-Fuhrmann and Silgoner 2018;Happ et al 2018;Preston and Wright 2019). While most studies find these differences when the construct is modelled onedimensionally 1 (Rudeloff et al 2019), there are some studies that model financial literacy multi-dimensionally and find differences in partial facets in favor of women.…”
Section: Gendermentioning
confidence: 99%
“…These differences are often attributed to different individual dispositions, such as interest in financial issues (e.g., Brown and Graf 2013;Lührmann et al 2015) or differences in socialisation patterns and learning opportunities (e.g., Rinaldi 2017;Rudeloff 2019). However, despite the fact that all these aspects are plausible and show to have a certain explanatory power, available research (e.g., Fonseca et al 2012;Greimel-Fuhrmann and Silgoner 2018;Rudeloff et al 2019) also suggests that even after considering them, a quite large portion of the performance differences between the various groups of test-takers remains unexplained. Consequently, further research on alternative explanations is required.…”
Section: Introductionmentioning
confidence: 99%